2000
DOI: 10.1111/j.1365-2621.2000.tb13582.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Konjac Blends and Soy Protein Isolate as Fat Replacements in Low‐fat Bologna

Abstract: Low-fat bolognas (LFB, < 2.0% fat) were developed with 2 levels (0.5% or 1.0%) of konjac blends (KB, KSS = konjac flour/starch and KNC = konjac flour/carrageenan/starch) and the replacement of meat proteins with 2% soy protein isolate (SPI, DWB). Increased levels of KB decreased (P < 0.05) lightness and yellowness, and most texture profile analysis (TPA) values. LFB containing 1.0% KB with 2% SPI addition had TPA values and sensory flavor/ taste attributes similar to the control (CTL II, 30% fat), whereas LFB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 25 publications
0
34
0
5
Order By: Relevance
“…In addition, Ahamed et al (2000) reported that cutlets containing egg white powder had a significantly higher pH compared to the control because of the higher pH of the egg white powder. Furthermore, Chin et al (2000) found that mean pH values of low-fat bologna containing ISP were higher than those of low-fat bologna formulated without ISP.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, Ahamed et al (2000) reported that cutlets containing egg white powder had a significantly higher pH compared to the control because of the higher pH of the egg white powder. Furthermore, Chin et al (2000) found that mean pH values of low-fat bologna containing ISP were higher than those of low-fat bologna formulated without ISP.…”
Section: Resultsmentioning
confidence: 98%
“…Hsu and Chung (1999) found that the addition of konjac decreased the hardness in low fat Kung-wan (a Taiwanese emulsified meatball), and Chin et al (1998) reported that as the levels of konjac blends increased from 0.5 to 1.0%, the TPA hardness of low-fat bologna decreased. In addition, Chin et al (2000) demonstrated that the gelation of konjac blends and a soy protein isolate upon cooking contributed to the viscoelastic texture of a low-fat meat gel system. Chen et al (1993) also reported that egg white improved the textural properties of surimi gels.…”
Section: Shear Force and Mfimentioning
confidence: 99%
“…The fat content of all MCP sausages was lower (p<0.05) than the low fat control (T 1 ). The reduction in fat content with incorporation of fat replacers was also reported by Berry (1994) in pork nuggets (gums and modified starches), Zanardi et al (2006) in salame milano (skimmed milk and dextrins) and Chin et al (2000) in bologna (soya protein isolate). The cholesterol level did not differ with increasing levels of MCP but 2% MCP sausages had lower (p<0.05) cholesterol content than others.…”
Section: Introductionmentioning
confidence: 90%
“…Proteins from soybean are commonly used in processed meat products due to their low cost and functional properties. Soy proteins are known for water-binding, fat-binding, and supporting high emulsion stability (Chin et al, 2000); hence, soy protein isolates (SPI) and concentrates are widely used in the preparation of chopped meats (Gordon and Barbut, 1991). However, addition of SPI occasionally gives less desirable palatability and allergen issue to meat products (Ho et al, 1997), and hence there are regulations to restrict their use in meat products.…”
Section: Introductionmentioning
confidence: 99%